Inside Cover: The Structure of Linkers Affects the DNA Binding Properties of Tethered Dinuclear Ruthenium(II) Metallo‐Intercalators (Chem. Eur. J. 23/2017). Issue 23 (22nd February 2017) - Saeed, Hiwa K.; Saeed, Ibrahim Q.; Buurma, Niklaas J.; Thomas, Jim A.
Abstract : Research into linked dinuclear Ru(dppz) DNA metallo‐intercalators demonstrates that binding affinities and thermodynamic signatures are profoundly influenced by the non‐intercalating tether ligand. The coordination "anchor point" of the linker, the incorporation of hydrogen bonding moieties, and its rigidity all modulate enthalpy and entropy contributions to the binding process. They even determine the balance between intercalation and groove binding. More information can be found in the Full Paper by J. A. Thomas et al. on page 5467 ff.